Barriers Associated with Seasonal Influenza Vaccination among College Students. (24th March 2016) - Benjamin, Stephanie M.; Bahr, Kaitlin O.
Abstract : Influenza can spread rapidly on college campuses because of high-density living conditions and frequent social interactions. However, seasonal influenza vaccination rates on college campuses are low. The purpose of this study is to identify barriers associated with receipt of the seasonal influenza vaccination. Questionnaires were completed by a convenience sample of 383 undergraduate students in January 2014. Data were analyzed to identify barriers associated with receiving the seasonal influenza vaccine. Only 20.6% of students reported receiving the vaccine within the last 6 months. Among students who did not receive the vaccine, 47.8% believed they would get influenza from the vaccine, 41.6% believed the vaccination may have dangerous side effects, and 39.6% believed they were not at risk for contracting influenza. The majority of nonvaccinated students did not believe cost of the vaccine or access to the vaccine were barriers. Many college students are not receiving the seasonal influenza vaccine, representing an important area for improvement. Understanding potential barriers associated with receipt of this vaccine is important for identifying and creating effective public health education programs and campaigns. There is a need for enhanced vaccination education efforts among college students, particularly with respect to the safety and importance of this vaccine.